Thawing of snow and ice caused extraordinary high and fast mercury fluxes to lake sediments in Antarctica. (1st March 2019) - Pérez-Rodríguez, Marta; Biester, Harld; Aboal, Jesús R.; Toro, Manuel; Martínez Cortizas, Antonio
Abstract: Due to its biomagnification mercury (Hg) is an element of concern especially in the remote pristine ecosystems such as Antarctica. Despite the sensitivity of the region, there is still a limited knowledge about the influence of natural processes, i.e. volcanism, climate, atmospheric mercury depletion events or freeze-thawing cycles, on the Hg cycle in Antarctica. We analysed total Hg and solid phase Hg species (Hg-thermo–desorption-AAS) in 1600 years old sediments from Limnopolar Lake (Byers Peninsula, South Shetland Islands). Some sections of the core show unusual high Hg concentrations (1141–11286 ng g −1 ) and accumulation rates (310–4902 µg m −2 yr −1 ). Hg-thermo-desorption analyses indicate that Hg is bound in the sediment by organic matter of different degree of degradation. We propose a combination of different natural processes to explain the high enrichment of Hg in the sediments. The nearby (30 km) Deception Island volcano appears to be the main source of Hg, while climatic conditions have controlled freezing-thawing of the ice-cover and the enrichment of Hg in the snowpack on the frozen lake (and its catchment). The release of Hg from the snowpack during thawing events appears to cause the extreme Hg enrichment in the sediments. The global atmospheric pollution is a minority signal in our record. The ∼2.2 fold increase in Hg concentrations since AD ∼ 1860 points industrial activities as the unique pollution cause. Our findings indicate that thawing of Antarctic ice might release large quantities of Hg to freshwater and marine systems and related food chains.